The Impact Of Multidisciplinary Lifestyle Interventions On The Health Of Patients With Diabetes Mellitus - Selano, Maria; Handayani, Kristiana Prasetia; Damayanti , Ariani (Journal of Health Empowerment and Interprofessional Practice, 2026)
Background of the Study: Diabetes mellitus is a growing global health problem, including in Indonesia, with a prevalence expected to reach 12% by the year 2025. This disease affects the quality of life and imposes a significant economic burden.Objectives and Scope of the Paper: The present research investigates how integrated lifestyle modifications encompassing nutritional guidance, physical exercise, psychological counseling, and health literacy affect the well-being of diabetic individuals at the Kagok Public Health Center in SemarangMethods: The research design used is a quasi-experimental design with two groups of pre-test and post-test. The sample consists of 60 patients with diabetes mellitus divided into an intervention group (n=30) and a control group (n=30). Evaluation was conducted over one month using a self-efficacy questionnaire and measurements of fasting blood glucose levels, blood pressure, and body mass index (BMI). Data analysis was performed using the Shapiro-Wilk normality test and the Mann-Whitney test for intergroup comparisons.Results: The study results indicate a significant increase in self-efficacy scores, as well as a decrease in blood glucose levels and blood pressure in the intervention group compared to the control group, with a p-value of < 0.05.Conclusion: Evidence from this study confirms that integrated lifestyle management significantly bolsters both clinical health outcomes and the perceived quality of life among diabetic populations. These insights serve as a cornerstone for designing specialized training curricula for clinicians and establishing enduring health intervention frameworks within the Indonesian context.